2020
DOI: 10.1002/bmc.4731
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bioavailability of two zolpidem hemitartrate formulations in healthy human Brazilian volunteers using high‐performance liquid chromatography coupled to tandem mass spectrometry

Abstract: To assess the bioequivalence of two zolpidem hemitartrate formulations in 30 healthy volunteers. Plasma samples were obtained over a 24 h period. Plasma concentrations of zolpidem were analyzed by liquid chromatography coupled to tandem mass spectrometry with positive ion electrospray ionization using multiple reaction monitoring. Values of peak concentration (Cmax), area under curve (AUC), half‐life, elimination constant, volume of distribution and clearance showed statistically significant differences when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Both reference and test products for 5 mg sublingual formulations showed a maximum plasma concentration Cmax of 98.753 ng/mL and 105.737 ng/mL, respectively, consistent with the values found by other authors [29,34].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Both reference and test products for 5 mg sublingual formulations showed a maximum plasma concentration Cmax of 98.753 ng/mL and 105.737 ng/mL, respectively, consistent with the values found by other authors [29,34].…”
Section: Discussionsupporting
confidence: 90%
“…Forty study subjects were to participate in this study in order to meet the requirements of nominal significance level of 50 %, 2x2 crossover design, 80-125% equivalence range, 28% maximum CVintra for pharmacokinetic parameters, population ratio between 95-105% for treatment average plus an additional number of 8 volunteers to compensate possible losses due to dropout/exclusions. The planned number of subjects for the study is consistent with studies reported buy some authors [29][30][31] and higher than the number estimated by other [10,32]. The study was completed with 38 subjects, an amount higher than the 32 estimated volunteers in case of loss of the 8 subjects considered in the sample size determination, fact which contributed to maintain the obtained test power for pharmacokinetic parameters near 100%.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thereafter, the fitted parameter values were transferred to PK‐Sim, and the specific intestinal permeability was fitted to pharmacokinetic data in the fasted state from multiple clinical studies 27,28,31–33 . Another independent set of clinical data not used during parameter optimization was thereafter used to evaluate the adult PBPK model 34–45 …”
Section: Methodsmentioning
confidence: 99%
“…Several analytical methods have been reported for the quantification of zolpidem in blood, including HPLC with fluorescence detection [ 2 , 10 ], HPLC-DAD [ 11 ], GC/MS [ 12 ], GC/MS/MS [ 13 ], LC/MS [ 8 , 14 ], UPLC/MS [ 15 ], LC/MS/MS [ 16 , 17 , 18 , 19 , 20 , 21 ], and UHPLC-MS/MS [ 5 , 22 , 23 ]. The most commonly used techniques for zolpidem extraction from biological matrices are liquid–liquid extraction (LLE) [ 2 , 5 , 14 , 16 , 19 , 20 , 21 ] and solid-phase extraction (SPE) [ 8 , 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%